Upaya Peningkatan Hasil Belajar Siswa Pada Materi Waktu dan Durasi Dengan Menggunakan Media Papan Waktu - Atmasita, Anisa Putri; Raharjo, Resdianto Permata (Jurnal Riset Madrasah Ibtidaiyah, 2024)
The purpose of this study is to improve the learning outcomes of students in Grade II Elementary School State Diwek 1 Jombang by using the Learning media time board for mathematics material material time and duration. At the elementary school level, students have difficulty in capturing abstract explanations, so an introductory learning tool is needed. Time board Media can be used to facilitate educators in the learning process and can be applied manually by students, so as to facilitate students in understanding how to calculate time and can improve student learning outcomes. This study uses quantitative methods with quasi experimental design and the design used is one group pretest postest design. Data analysis techniques used in this study is the Wilcoxon test with the help of SPSS 23.00 for windows. Based on the results of research that has been done shows that the application of time board media in the learning process can increase the value of student learning outcomes by an average of 9.50. By comparing the value of pre-test and post-test student learning outcomes have increased significantly.